Planning mobility in Portugal with a gender perspective - Queirós, Margarida (2020)
According to Greed (2012), historical developments of the urban planning policy resulted in cities being based upon land-use zoning, separating home from work, thus extended commuting time, and enclosed housing estates mostly for women. Therefore, a dispersed land-use was developed, based on the rational planning paradigm supported by the use of the car. Consequently, daily tasks are allocated between motorised displacements, on traffic-jammed roads. Normally, it is women who are most likely responsible for daily home routines, childcare and shopping but, at the same time, with a professional activity outside the home, their mobility patterns are differentiated from men’s. Normally, women combine home and work tasks in a more complex trip-chain than the traditional home-to-work pattern. When residential places are separated from working areas, as a result of a spatial functionality idea created by the modern movement during the twentieth century, women need a greater amount of public transport services, with transverse inter-area bus routes and off-peak services. As an outcome, transport planning policies have paid little attention to gender transport pattern differences, assuming that transport interventions are gender neutral [...]